2013
DOI: 10.1024/1661-8157/a001485
|View full text |Cite
|
Sign up to set email alerts
|

Gewaltbedingte Verletzungen in einem städtischen Umfeld aus Sicht einer unfallchirurgischen Notfallaufnahme

Abstract: Violence is a growing problem worldwide. In Switzerland, interpersonal violence seems to be an increasing problem as well. The aim of the current study was to describe a comprehensive picture of violence in a swiss city with regard to medical and social aspects. A total of 1740 patients injured by violent crimes between April 2004 and January 2011 were enrolled into this study. Most of them were male. There were no relevant changes regarding the number of within the observation period. However, the proportion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Males from Poland and Sweden are often engaged in manual labour and are therefore exposed to more work-related injuries and accidents, possibly explaining their over-representation at the trauma clinic [ 27 , 28 ]. In addition, males are generally more involved in violence and crime [ 29 ]. Studies have also shown that immigrant women of non-Western origins are less physically active and have lower levels of engagement in sports activities, which may explain their under-representation at the trauma clinic [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Males from Poland and Sweden are often engaged in manual labour and are therefore exposed to more work-related injuries and accidents, possibly explaining their over-representation at the trauma clinic [ 27 , 28 ]. In addition, males are generally more involved in violence and crime [ 29 ]. Studies have also shown that immigrant women of non-Western origins are less physically active and have lower levels of engagement in sports activities, which may explain their under-representation at the trauma clinic [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%